Finite control of dielectric constant with magnetic field in Sm-doped Ba-Co U-type hexaferrites - Malhi Parambir Singh; Kumar Sachin; Singh Mandeep; Singh Anupinder; Sood Ashwani Kumar (Processing and Application of Ceramics, 2023)
Emergence of memory devices based on magneto-electric coupling leads us to investigate the dielectric and magneto-dielectric properties of U-type hexaferrites. (Ba1-3xSm2x)4Co2Fe36O60 ceramics, where x = 0.0-0.25, with the interval of 0.05, have been produced via auto combustion method and sintering at 1200°C. Every sample has an RЇ3m symmetric hexagonal structure, according to the XRD study. The samples with lower Sm content, i.e. 0.0 < x < 0.15 have better magnetic properties than the samples having 0.15 < x < 0.25. Impedance spectroscopy has been used to study dielectric characteristics. The sample with x = 0.15 at 1.2 T and 1000Hz showed maximum magnetization and a magneto-electric coupling accompanied by a magnetic coefficient of about 104.9%, which is very high in case of hexaferrites. Therefore, these results will be fruitful from the application point of view.